Four-Tier Diagnostic Test Assisted Website for Identifies Misconceptions Heat and Temperature - Evi Septiyani; Dwi Nanto (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2021)
Misconceptions get special attention in educational research because they are inhibiting students in learning. Misconceptions often occur in learning physics, especially the concept of heat, and nearly every sub-concept of physics on students experience various misconceptions. One of them is defining heat. Many students believe that temperature is considered as a unit of measure for the amount of heat. This is a wrong conception. Thus, it needs to be identified using appropriate diagnostic test instruments to reduce students’ misconceptions. Four-tier diagnostic tests can detect students’ misconceptions because they can dig deeper into understanding students’ conceptions. Unfortunately, the diagnostic tests of student misconception are still rarely applied at most schools. The reason is time constraints in the implementation and correction of the diagnostic tests. Therefore, here we report digital four-tier diagnostic test instruments of student misconception on heat and temperature through a helpful website and can be accessed anywhere.